IM, instant messaging, security - Rittinghouse, John W.; Ransome, James F. (Amsterdam ; Boston : Elsevier Digital Press, 2005)
BRIEF DESCRIPTION OF CONTENT: There is a significant need for a comprehensive book addressing the operational and day-to-day security management requirements. IM, used in enterprise networks can easily be reconfigured and allow for potentially nonstop exposure; they require the level of security be scrutinized carefully. This includes inherent security flaws in various network architectures that result in additional risks to otherwise secure converged networks. A few books cover components of the architecture, design, theory, issues, challenges, and recommended policies for IM security, but none of them address IM issues in a manner that is useful for the day-to-day operations and management of enterprise networks. IM Security is intended to bridge this gap. UNIQUE FEATURE/RATIONALE There are no current books that cover components of the architecture, design, theory, issues, challenges, and recommended policies for IM security. No book we know of addresses IM security in a manner useful for day-to-day operations and management of IM-capable networks in todays corporate environment.
Introduction; How Does IM Work?; IM Standards and Protocols; IM Malware; IM Security Risk Management; IM Risk Management for Enterprise; The Business Value of IM; The Future of IM (contributed by Tony Dubendorf); Acronyms; Glossary; Related Web Sites; -- References; Index.
Includes bibliographical references and index.
Keywords: Instant messaging -- Security measures; Electronic mail messages -- Security measures; Computer security; Electronic books